In Vivo Monitoring of Adult Neurogenesis in Health and Disease - Couillard-Despres, Sebastien; Vreys, Ruth; Aigner, Ludwig; Van Der Linden, Annemie (Frontiers in Neuroscience, 2011)
Adult neurogenesis, i.e. the generation of new neurons in the adult brain, presents an enormous potential for regenerative therapies of the central nervous system (CNS). While 5-bromo-2'-deoxyuridine (BrdU) labeling and subsequent histology or immunohistochemistry for cell type-specific markers is still the gold standard in studies of neurogenesis, novel techniques and tools for in vivo imaging of neurogenesis have been recently developed and successfully applied. Here, we review the latest progress on these developments, in particular in the area of magnetic resonance imaging (MRI) and optical imaging. In vivo in situ labeling of neural progenitor cells with micron-sized iron oxide particles (MPIOs) enables longitudinal visualization of endogenous progenitor cell migration by MRI. The possibility of genetic labeling for cellular MRI was demonstrated by using the iron storage protein ferritin as the MR reporter gene. However, reliable and consistent results using ferritin imaging for monitoring endogenous progenitor cell migration have not yet been reported. In contrast, genetic labeling of neural progenitor cells with a fluorescent or bioluminescent reporter has led to the development of some powerful tools for in vivo imaging of neurogenesis. Here, two strategies, i.e. viral labeling of stem/progenitor cells and transgenic approaches, have been used. In addition, the use of specific promoters for neuronal progenitor cells such as doublecortin increases the neurogenesis specificity of the labeling. Naturally, the ultimate challenge will be to develop neurogenesis imaging methods applicable in humans. Therefore, we certainly need to consider other modalities such as positron emission tomography (PET) and proton magnetic resonance spectroscopy (1H-MRS), which have already been implemented for both animals and humans. Further improvements of sensitivity and neurogenesis-specificity are nevertheless required for all imaging techniques currently available.